A novel computerized assessment of manual spatial exploration in unilateral spatial neglect. Issue 6 (3rd July 2022) - Pierce, Jordan E.; Ronchi, Roberta; Thomasson, Marine; Rossi, Irene; Casati, Carlotta; Saj, Arnaud; Vallar, Giuseppe; Vuilleumier, Patrik
ABSTRACT: Unilateral spatial neglect is a neuropsychological syndrome commonly observed after stroke and defined by the inability to attend or respond to contralesional stimuli. Typically, symptoms are assessed using clinical tests that rely upon visual/perceptual abilities. However, neglect may affect high-level representations controlling attention in other modalities as well. Here we developed a novel manual exploration test using a touch screen computer to quantify spatial search behaviour without visual input. Twelve chronic stroke patients with left neglect and 27 patients without neglect (based on clinical tests) completed our task. Four of the 12 "neglect" patients exhibited clear signs of neglect on our task as compared to "non-neglect" patients and healthy controls, and six other patients (from both groups) also demonstrated signs of neglect compared to healthy controls only. While some patients made asymmetrical responses on only one task, generally, patients with the strongest neglect performed poorly on multiple tasks. This suggests that representations associated with different modalities may be affected separately, but that severe forms of neglect are more likely related to damage in a common underlying representation. Our manual exploration task is easy to administer and can be added to standard neglect screenings to better measure symptom severity.